The Role of Neoadjuvant Surgical Intervention in the Primary and Repeat Treatment of Malignant Brainstem Tumors in Children and Adolescents - V. A. Solodkiy; T. R. Izmaylov; G. A. Pan'shin; Z. S. Tsallagova; O. S. Regentova (Вестник рентгенологии и радиологии, 2019)
Objective. To study and analyze the significance of the degree and possibility of surgical resection of a brainstem tumor in children and adolescents on the results of treatment in relation to various prognostic factors.Material and methods. This investigation enrolled 102 children with a brainstem tumor. A morphological study was not performed because of the location of the tumor and the inability to perform a surgical intervention. The patients’ mean age was 7.1 ± 3.4 years. The results of the study were assessed in terms of overall cumulative survival rates.Results. Primary chemoradiotherapy was performed in 52 of the 102 patients; 50 children underwent repeat chemoradiotherapy. In the entire group, 89 (87%) patients received no surgical treatment;  while subtotal resection or ventriculoperitoneal bypass surgery (VBS) could be done in 13 (13%) children; the median follow-up of the entire group was 19.2 weeks. In the study groups, the statistical  differences in overall survival rates were significant (Log-Rank p = 0.044).Conclusion. Regardless of primary or repeat  radiotherapy  and  chemotherapy, surgical intervention, including VBS in children and adolescents, significantly affects overall survival rates.